Measuring the Quality of Personal Care in Patients Undergoing Radiotherapy for Prostate Cancer. Issue 12 (December 2017) - Foley, K.A.; Groome, P.A.; Feldman-Stewart, D.; Brundage, M.D.; Foley, J.H.; McArdle, S.; Mackillop, W.J.
Abstract: Aims: To describe the quality of the non-technical component of the care (personal care) of patients receiving radical radiotherapy for prostate cancer and to identify elements of personal care that should be priorities for quality improvement. Materials and methods: One hundred and eight patients undergoing radiotherapy for localised prostate cancer completed a self-administered questionnaire that asked them to rate the importance of 143 non-technical elements of care and to rate the quality of their own care with respect to each element. The elements that a patient rated as both 'very important' and less than 'very good' were deemed to be his priorities for improvement. The priorities of the population were established by ranking the elements based on the percentage of patients who identified them as a priority (importance/quality analysis). Results: The response rate was 65%. The percentage of elements rated 'very good' varied from patient to patient: median 79% (interquartile range 69–92%). The percentage of elements rated either 'very good' or 'good' was higher: median 96% (interquartile range 86–98%). Nonetheless, almost every patient rated at least some elements of his care as less than optimal, regardless of the cut-off point used to define optimal quality. Patients assigned their lowest quality ratings to elements relating to the quality of the treatment environment and comprehensiveness of additional services available to them. However, patients rated most of these elements as relatively unimportant, and importance/quality analysis identified elements of care relating to communication of information about the disease and its treatment as the highest priorities for quality improvement. Conclusions: Most patients rated most elements of their personal care as very good, but almost all were able to identify some elements that were less than optimal. When ratings of quality were integrated with ratings of importance, elements relating to communication emerged as the patients' highest priorities for quality improvement. Highlights: Men receiving prostate radiotherapy rated the quality of non-technical elements of their care. Most men rated most elements as very good, but almost all rated some as suboptimal. Elements rated low in quality and high in importance were deemed priorities for quality improvement. Elements of communication between caregivers and patients emerged as top priorities.